Implementation and Evaluation of the Carrera Program for Delaying Teen Sex in Georgia - Tressa Tucker; Mary Langley (Georgia Southern University, 2016)
Background: In three geographic areas in Georgia, rural, micropolitan, and urban, Morehouse School of Medicine (MSM) implemented the evidence-based Children's Aid Society Carrera Program at community organizations with Boys and Girls Clubs (BGCs) as the comparison group. This study attempted to replicate the findings of reduced teen pregnancy and birth found for the New York Carrera Program. Methods: For this longitudinal study with a quasi-experimental design, the sample included 400 youth who were in 6th or 7th grade. A total of 220 were enrolled in the intervention group and 180 in the comparison group. The study was performed in the fall of 2012, 2013, and 2014. The following data sources were utilized: paper-and-pencil surveys, daily attendance, component attendance, observation forms, focus groups, and interviews. There was one analytic sample (N = 204) for the primary research questions. Data were pooled separately across the intervention and the comparison sites. A hierarchical logistic regression model was used to test for program impact. Covariates included selected demographic variables, site geography (urban vs. rural), and previous sexual history. For answering the two primary research questions the 0.025 significance level was used to adjust for multiple comparisons. Results: After one year of the intervention, the Carrera group was significantly lower in "ever had sex" than the BGC group. At years two and three, however, there were no appreciable differences between these two groups, a result possibly due to implementation issues, particularly attendance. Conclusions: When implemented with fidelity, Carrera can have a positive effect, even in rural communities. Programs should seek to achieve the required intervention dosage and address the reasons why teen pregnancy is often higher in these communities.